Effect of Triple Therapy on Cardiovascular and Severe Cardiopulmonary Events in Chronic Obstructive Pulmonary Disease: A Post Hoc Analysis of a Randomized, Double-Blind, Phase 3 Clinical Trial (ETHOS) - Singh, Dave; Martinez, Fernando J; Hurst, John R; Han, MeiLan K; Gale, Chris P; Fredriksson, Martin; Kisielewicz, Dobrawa; Mushunje, Alec; Movitz, Charlotta; Ojili, Nikki; Parikh, Himanshu; Arya, Niki; et al. (American journal of respiratory and critical care medicine, 2025)
Chronic obstructive pulmonary disease (COPD) is associated with an increased risk of cardiovascular and cardiopulmonary events. In the phase III, 52-week ETHOS trial (NCT02465567), triple therapy with budesonide/glycopyrrolate/formoterol fumarate (BGF) reduced rates of moderate/severe exacerbations and all-cause mortality compared with dual therapy with glycopyrrolate/formoterol fumarate (GFF) or budesonide/formoterol fumarate (BFF). However, the effect of BGF on cardiovascular events versus GFF remains unevaluated. Furthermore, the effect of BGF on time to first severe exacerbation has not been reported. To assess the effects of BGF 320/18/9.6 μg (BGF 320) and other inhaled corticosteroid-containing arms on cardiovascular and severe cardiopulmonary endpoints versus GFF in patients with COPD from the ETHOS trial. Patients with moderate to very severe COPD and a history of exacerbations were randomized to twice-daily BGF 320, BGF 160/18/9.6 μg, BFF 320/9.6 μg, or GFF 18/9.6 μg (GFF). Time to first severe COPD exacerbation was a prespecified endpoint; cardiovascular and severe cardiopulmonary endpoints included time to first major adverse cardiac event, time to first cardiovascular adverse event (AE) of special interest, time to first cardiac AE, and time to the composite endpoint of first severe cardiopulmonary event. BGF 320 reduced the rate of first occurrence (hazard ratio [95% confidence interval]) of cardiovascular and severe cardiopulmonary events versus GFF, including for time to first cardiovascular adverse event of special interest (0.63 [0.48, 0.82]), cardiac AE (0.60 [0.48, 0.76]), and severe cardiopulmonary event (0.80 [0.67, 0.95]). BGF had a benefit on cardiovascular endpoints and severe cardiopulmonary events versus GFF in patients with moderate to very severe COPD.